Econometric Analysis of the Economic Trilemma in Papua Province: Evidence from Growth, Inflation, and Unemployment Dynamics - Yundy Hafizrianda; Charley M. Bisay; Ida Ayu Purba Riani; Marsi Adi Purwadi (Institut Bisnis dan Informatika Kesatuan, 2025)
Papua’s economy illustrates the challenge of the Mundell-Fleming trilemma, where rapid growth led by extractive industries has not generated broad-based employment or stable prices. This study examines how the trilemma manifests at the Papua Province. Using monthly time-series data, econometric analysis was conducted through stationarity, classical assumptions, and regression tests. The results show an imperfect trilemma pattern. In the inflation model, economic growth significantly increases inflation, though with a small effect (0.0323), consistent with demand-pull theory. In the unemployment model, growth reduces unemployment as expected by Okun’s Law, but the impact is minimal (−0.0056), indicating that growth remains weakly labor-intensive. More unexpectedly, inflation is found to increase unemployment (0.0229), contradicting the Phillips Curve, which predicts the opposite relationship. These findings suggest that Papua does not experience the classic trilemma trade-offs in a consistent manner. Policy implications include cautious monetary measures that consider threshold effects of growth, inflation, and unemployment, alongside fiscal strategies focused on productivity, infrastructure development, and strengthening labor-intensive sectors to achieve more inclusive growth.